Comment on "The effects of molecular weight and thermal decomposition on the sensitivity of a thermal desorption aerosol mass spectrometer". Issue 9 (1st September 2016) - Jimenez, Jose L.; Canagaratna, Manjula R.; Drewnick, Frank; Allan, James D.; Alfarra, M. Rami; Middlebrook, Ann M.; Slowik, Jay G.; Zhang, Qi; Coe, Hugh; Jayne, John T.; Worsnop, Douglas R.
Abstract : Copyright © American Association for Aerosol Research